OP0123 Body mass index and physical activity as risk factors for primary osteoarthritis. a cohort study in 50.034 persons. (1st June 2001) - Flugsrud, GB; Espehaug, B; Havelin, LI; Nordsletten, L; Meyer, HE
Abstract : Background: As no cure exists for osteoarthritis other than operation, it is important to identify preventable aetiological factors. Objectives: To describe the association between middle age body mass index (BMI) and physical activity, and later total hip replacement (THR), in a large cohort. Methods: The Norwegian Arthroplasty Register records all THRs and hip revisions performed in Norwegian hospitals. 1 In three Norwegian counties the National Health Screening Service (NHSS) three times conducted a cardiovascular screening during the years 1974–88. Persons born 1925–42 were screened repeatedly at median ages 42, 47 and 53 years. 2 For 89% of the participants data on body weight and height were available at the NHSS from a screening for tuberculosis, conducted during the years 1963–75 (median age 34 years). 3 The registers were matched and survival analyses performed using the Cox regression model. An event was recorded when a person had his first THR for primary osteoarthritis. Follow up was 1989–98. We controlled for age at screening, body height, marital status and smoking. Results: Analysing screening data from the second cardiovascular screening only (attendance 92.8%) we found 672 THRs. A dose-response relationship was found between BMI and the risk for THR. Women in the highest BMI quarter had a relative risk of 3.0 (95% CI 2.2–4.2) compared to women in the lowest quarter. The corresponding figure in men was 2.0 (95% CI 1.5–3.0). Physical activity at work also showed a dose-response relationship. Both women and men in the most active group had a relative risk for THR of 2.1 compared to the least active group. Analyses of BMI data from each of the four screenings indicated that the predictive value of BMI for later THR was strongest at the tuberculosis screening and decreased gradually and considerably at the following screenings. Conclusion: This study confirmed that high physical activity at work increases the risk for THR-demanding osteoarthritis in men. Contrary to earlier findings, the effect was equally strong among women in our population. We found that even for levels of BMI and physical activity at work that were well within the normal ranges an increment in these risk factors increased the risk for THR-demanding osteoarthritis. Our findings indicate that the peak impact of BMI on the development of hip osteoarthritis may be at, or before, the age of 34 years. References: Havelin LI, Espehaug B, Vollset SE, Engesæter LB, Langeland N. The Norwegian Arthroplasty Register. A survey of 17, 444 total hip replacements. Acta Orthop Scand. 1993;64:245–51 National Health Screening Service, The cardiovascular disease study in Norwegian counties: results from second screening. Oslo: National Health Screening Service, 1988 Waaler HT. Height, weight and mortality. Acta Med Scand Suppl. 1984;679:1–56